Reforming the Common European Asylum System Opportunities, Pitfalls, and Downsides of the Commission Proposals for a New Pact on Migration and Asylum - Thym, Daniel; Odysseus Academic Network (Schriften zum Migrationsrecht, 2022)
Timely and profound collection of high-quality contributions, written by experts from across Europe, on the ongoing policy debate on the reform of Common European Asylum System. Contributions combine an in-depth presentation with a style of argument that addresses a broader audience: fellow academics, students and PhD researchers, practitioners, and political actors. Attention to the legislative detail coincides with an awareness of the broader picture in terms of policy developments, human rights computability, and practical implementation on the ground. The edited volume allows readers to understand the complex rules and to identify overarching challenges defining European asylum policy at this juncture. With contributions by Dr. Ulrike Brandl, Dr. Galina Cornelisse, Prof. Philippe De Bruycker, Jean-Baptiste Farcy, Prof. Paula García Andrade, Prof. Dr. Iris Goldner Lang, Prof. Elspeth Guild, Dr. Meltem İneli Ciğer, Dr. Lyra Jakuleviciene, Prof. Francesco Maiani, Dr. Madalina Bianca Moraru, Prof. Violeta Moreno-Lax, Prof. Sylvie Sarolea, Dr. Lieneke Slingenberg, Prof. Dr. Daniel Thym, Prof. Lilian Tsourdi and Prof. Jens Vedsted-Hansen.